KUTKM di Radio 3 Negeri Sembilan - Safei, Su'aidi (KUTKM, 2003)
This radio show broadcasted widely in Negeri Sembilan and Putrajaya. The invited speaker, Assoc.Prof.Dr.Hj.Su'aidi touched on various issues concerning National Technical University College of Malaysia (KUTKM) such as hands-on concept, development of the university, the role of the Office of Students Affair  and student activities/ programs. All this accomodate the agenda towards producing world-class technical graduates.